Balance Rehabilitation Unit (BRU TM) posturography in relapsing-remitting multiple sclerosis - Natália Kessler; Maurício Malavasi Ganança; Cristina Freitas Ganança; Fernando Freitas Ganança; Sabrina Chiogna Lopes; Ana Paula Serra; Heloisa Helena Caovilla (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate balance control with Balance Rehabilitation Unit (BRU TM) posturography in patients with multiple sclerosis (MS). METHOD: A cross controlled study was performed including 39 relapsing-remitting multiple sclerosis patients with scores less than or equal to 4 in the Expanded Disability Status Scale (EDSS), and a homogeneous control group consisting of 65 healthy individuals, matched by the age and gender. The experimental group was distributed according to the EDSS scale scores in 0-2.5 and 3-4. To assess the vestibular system function, the patients underwent a neurotological evaluation, including posturography of the Balance Rehabilitation Unit (BRU TM). RESULTS: Statistically significant differences were observed when comparing the values of the sway velocity and the ellipse area of the MS 0-2.5 group with the control and the MS 3-4 group with the control. A statistically significant difference was verified between the MS 0-2.5 and the MS 3-4 groups in the condition 3 ellipse area values. CONCLUSION: The evaluation of the balance control with posturography of Balance Rehabilitation Unit (BRU TM) enables the identification of abnormalities of the sway velocity and confidential ellipse in patients with relapsing-remitting multiple sclerosis.